Answer:
½
Explanation:
f(4) = 2
(f^-1)(4) = 6
Because f(6) = 4
f((f^-1)(x)) = x
[f((f^-1)(x))]' = f'(f^-1(x)) × (f^-1(x))'
(x)' = f'(f^-1(x)) × (f^-1(x))'
1 = f'(f^-1(x)) × (f^-1(x))'
At x = 4
1 = f'(6) × (f^-1(4))'
1 = 2 × (f^-1(4))'
(f^-1(4))' = ½
1/2
By definition of inverse functions:
f(f⁻¹(x)) = x
Take derivative using chain rule:
f'(f⁻¹(x)) (f⁻¹(x))' = 1
(f⁻¹(x))' = 1 / f'(f⁻¹(x))
Evaluate at x=4:
(f⁻¹(4))' = 1 / f'(f⁻¹(4))
(f⁻¹(4))' = 1 / f'(6)
(f⁻¹(4))' = 1 / 2
5.1m questions
6.7m answers